Restrictions during pandemic: justified but is it lawful? - Mažrimaitė, Andra; Pasvenskas, Vytautas (Vilnius University Open Series, 2021)
The article analyses if restrictions on business during the quarantines were proportionate and legitimate. The authors of this article argue that the forced closure of businesses during quarantine in its essence resembles the institute of taking private property ownership rights for public needs rather than restricting the freedom of economic activity because activities have been suspended entirely instead of merely being subject to certain operational restrictions. Such restrictions may be imposed only in exceptional cases and in the form of a law. It would be in line to consider proportionate compensations for businesses’ losses due to forcible closure from the State.